The sermons and other practical works: consisting of above one hundred and fifty sermons, besides his poetical pieces. To which is prefixed an account of the author's life and writings, with an elagiac poem and large contents - Erskine, Ralph (Printed by J. Bryce [etc.], 1777)
Vol.1-9: Sermons. -- V.10: Poetical works.